Pengaruh Karakteristik Individu dan Karakteristik Pekerjaan Terhadap Kinerja Pegawai Dengan Variabel Mediator Motivasi Kerja Pegawai Di Kantor Badan Pendapatan Daerah Kabupaten Kaimana - Mei Indrawati; Sri Mulyani; Yason Waryensi (Universitas 45 Surabaya, 2024)
Yason Waryensi, 2024. The Influence of Individual Characteristics and Job Characteristics on Employee Performance with Mediator Variables of Employee Work Motivation at the Kaimana Regency Regional Revenue Agency Office. Wijaya Putra University Postgraduate Program Surabaya. This type of research uses explanatory research, the research approach uses a quantitative approach. The research sample was 40 employees. The objectives of this research are 1) To describe individual characteristics, job characteristics, work motivation and employee performance. 2) To test and analyze the influence of individual characteristics on the work motivation of Kaimana Regency Regional Revenue Agency employees. 3) To test and analyze the influence of job characteristics on the work motivation of the Kaimana Regency Regional Revenue Agency. 4) To test and analyze the influence of work motivation on the performance of Kaimana Regency Regional Revenue Agency employees. 5) To test and analyze the influence of individual characteristics on the performance of Kaimana Regency Regional Revenue Agency employees. 6) To test and analyze the influence of job characteristics on the performance of Kaimana Regency Regional Revenue Agency employees. 7) To test and analyze the indirect influence of individual characteristics on employee performance with work motivation as a variable mediator at the Kaimana Regency Regional Revenue Agency. 8) To test and analyze the indirect influence of job characteristics on employee performance with work motivation as a mediator variable at the Kaimana Regency Regional Revenue Agency. The research results show that: 1) Individual characteristics, job characteristics, motivation and performance of Kaimana Regency Regional Revenue Agency employees are in the very good category. 2) Individual characteristics have a significant positive effect on the work motivation of Kaimana Regency Regional Revenue Agency employees. 3) Job characteristics have a significant positive effect on the work motivation of Kaimana Regency Regional Revenue Agency employees. 4) Work motivation has a significant positive effect on the performance of Kaimana Regency Regional Revenue Agency employees. 5) Individual characteristics have an insignificant positive effect on the performance of Kaimana Regency Regional Revenue Agency employees. 6) Job characteristics have a positive and insignificant effect on the performance of Kaimana Regency Regional Revenue Agency employees. 7) Individual characteristics have an indirect effect on employee performance with work motivation as a mediator variable at the Kaimana Regency Regional Revenue Agency. 8) Job characteristics have an indirect effect on employee performance with work motivation as a mediator variable at the Kaimana Regency Regional Revenue Agency.